Frontiers in eco-entrepreneurship research - Gary D. Libecap (Emerald, 2009)
Eco entrepreneurship (the provision of new products, processes, services with environmental benefits) is not well understood regarding its motives, returns, products, services, organization, and property rights. However, as public concern about the environment rises, understanding the relationship between entrepreneurship and the environment is increasingly important. This volume examines the environmental entrepreneur and the role of property rights in encouraging eco entrepreneurship, and uses micro economics to assess whether eco entrepreneurship is fundamentally different from more general entrepreneurship.
Keywords: Business & Economics -- Entrepreneurship.; Entrepreneurship.; Applied ecology.; elektronické knihy; electronic books